CERITA RAKYAT SEBAGAI MEDIA PEDAGOGIS DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR: TINJAUAN SYSTEMATIC LITERATURE REVIEW - Meitria Iintamara; Damanhuri Damanhuri; Ayu Reza Ningrum (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This study aims to synthesize trends, pedagogical focus, media forms, and the impact of the use of folklore as a pedagogical medium in Indonesian language learning in elementary schools for the 2019–2025 period. The study used a Systematic Literature Review (SLR) approach with PRISMA 2020 guidelines. Literature searches were conducted through Publish or Perish on the Scopus and Google Scholar databases, then selected using Covidence according to the stages of identification, screening, eligibility, and inclusion. Of the 113 initial articles, 11 articles met the inclusion criteria and were analyzed through thematic analysis and bibliometric mapping using VOSviewer. The results show an increase in publications since 2023 with a dominant focus on reading literacy and cultural literacy. Learning media has evolved from conventional text to visual-interactive media, immersive technology (Mixed Reality), and AI-assisted learning. Empirically, interactive media and structured technology have shown high effectiveness, while generative AI has not shown consistent statistical significance. This finding confirms that the effectiveness of folktales is more determined by the quality of instructional design than by the complexity of the technology, and provides a conceptual contribution in mapping the transformation of folktales from narrative teaching materials to adaptive pedagogical media in Indonesian language learning in elementary schools. ABSTRAK Penelitian ini bertujuan untuk mensintesis tren, fokus pedagogis, bentuk media, dan dampak pemanfaatan cerita rakyat sebagai media pedagogis dalam pembelajaran Bahasa Indonesia di sekolah dasar periode 2019–2025. Penelitian menggunakan pendekatan Systematic Literature Review (SLR) dengan pedoman PRISMA 2020. Pencarian literatur dilakukan melalui Publish or Perish pada basis data Scopus dan Google Scholar, kemudian diseleksi menggunakan Covidence sesuai tahapan identification, screening, eligibility, dan included. Dari 113 artikel awal, sebanyak 11 artikel memenuhi kriteria inklusi dan dianalisis melalui analisis tematik serta pemetaan bibliometrik menggunakan VOSviewer. Hasil menunjukkan peningkatan publikasi sejak 2023 dengan dominasi fokus literasi membaca dan literasi budaya. Media pembelajaran berkembang dari teks konvensional menuju media visual-interaktif, teknologi imersif (Mixed Reality), hingga AI-assisted learning. Secara empiris, media interaktif dan teknologi terstruktur menunjukkan efektivitas tinggi, sedangkan AI generatif belum menunjukkan signifikansi statistik yang konsisten. Temuan ini menegaskan bahwa efektivitas cerita rakyat lebih ditentukan oleh kualitas desain instruksional dibanding kompleksitas teknologi, serta memberikan kontribusi konseptual dalam memetakan transformasi cerita rakyat dari bahan ajar naratif menjadi media pedagogis adaptif dalam pembelajaran Bahasa Indonesia di sekolah dasar